(untitled) - Demoor, Marysa (New York, 2004)
Marketing the Authorlooks at the careers and the writings of a selection of authors writing in the period 1880-1930 (from the fairly unknown Emilia Dilke and Rosamund Watson to literary celebrities like Henry James, James Joyce and Virginia Woolf) who all impersonated identities which they had created for themselves. It argues that as a result of the socio-economic changes at the time authors had to remain in control of their public image in order to survive.
Keywords: English literature,Authors in literature,Authors and readers,Authorship; History and criticism,English-speaking countries,History,Marketing; 20th century,20th century